Solusi Al-Qur’an terhadap Persoalan Kemiskinan Umat: Revitalisasi Entrepreneur Milenial Berbasis Ekonomi Digital: Alek Saputra*, Redian Mulyadita, Dian Meliza - Alek Saputra; Redian Mulyadita; Dian Meliza (Samudra Publisher, 2023)
Indonesia is a Muslim-majority country, namely 207,176,162 of the total population of 237,641,326, or 87.18% of Indonesia's population is Muslim. However, from an economic perspective, Muslims in Indonesia do not constitute the majority in controlling assets. Becoming a young entrepreneur has recently become a hot topic for discussion. Considering the large number of millennials who are successful as entrepreneurs, they can lead to the development of a country's economy. However, becoming a millennial entrepreneur is not as easy as one might imagine, considering that in the online era, all gadgets can create laziness, thus creating people who lie down. For this reason, creating a generation of millennial entrepreneurs is an effort that must be developed by a country by instilling entrepreneurial values ​​into the millennial soul. Based on the personality and characteristics of a millennial entrepreneur who applies Islamic values ​​as a Muslim, this can be used as a reference for basic capital in his business activities. Judging from the problems above, the focus of the discussion in this article is a solution to the problem of people's poverty by emphasizing the revitalization of millennial entrepreneurs based on the digital economy as a breakthrough in the people's economy today